A genome-scale shRNA resource for transgenic RNAi in Drosophila. - Ni, J.Q.; Zhou, R.; Czech, B.; Liu, L.P.; Holderbaum, L.; Yang-Zhou, D.; Shim, H.S.; Tao, R.; Handler, D.; Karpowicz, P.; Binari, R.; Booker, M.; et al. (Nature Methods, 2011)
Existing transgenic RNAi resources in Drosophila melanogaster based on long double-stranded hairpin RNAs are powerful tools for functional studies, but they are ineffective in gene knockdown during oogenesis, an important model system for the study of many biological questions. We show that shRNAs, modeled on an endogenous microRNA, are extremely effective at silencing gene expression during oogenesis. We also describe our progress toward building a genome-wide shRNA resource.